KEKERASAN TERHADAP PEREMPUAN (Mengapa Masyarakat Terbiasa Lecehkan Perempuan ?) - Maimun, Agus (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
Men's subordination towards women still exists in public, social, political, economic as well as cultural areas. Consequently, that kind of social construction negates the representative of women's right due to fear of the present of women's body which trespasses religious and social norms. In fact, any religion and humanity refuse such kinds of discriminition or intimidation towards women.Â Harassment towards women can be analized through social, moral, emotional, motivational as well as consept of personalityÂ perspectives. As the alternative solution for aforementioned problems, efforts can be taken such as reinterpreties religious doctrines based on gender perspective, criticizies sexism myths, socializies gender equality to the society and establish the institution concerning gender issues.